Reclamations of brackishwater fishponds level on acid sulfate soils - Tirtoredjo, Alie Poernomo (College of Fisheries, University of the Philippines in the Visayas, 1983)
This study was conducted in 12 newly constructed fish ponds on acid sulfate soils at the Brackishwater Aquaculture Center (BAC) of the University of the Philippines in the Visayas,Leganes, Iloilo from September 1981 to April 1982. The study aimed a) to determine and evaluate the physico-chemical and chemical changes in soil and water of the acid sulfate ponds under different methods of reclamation, and b) to evaluate the effect of reclamation on the growth and production of benthic algae and the survival, growth and yield of milkfish. The experiment included three reclamation included three reclamation methods and a control. The treatments were: I.) No bottom tilling, no dike leaching but pond bottom drying during the reclamation (control); II.) No bottom tilling but trying and flushing of the pond bottom and dike leaching; III.) Tilling, drying and flushing of the pond bottom and dike leaching; IV.) Tilling, drying and flushing of the pond bottom but no dike leaching. There was an increase (1.1 to 1.2 units) in dry soil pH in treatments II, III and IV, but not in treatment I. The increase in pH in these treatments was associated with considerable decrease in the concentrations of potential acidity, exchangeable aluminum, active iron, pyritic iron, active manganese and acetate soluble sulfate. The lablab production (ash free dry weight) was highest (883.35 g/m2) in treatment IV, followed by treatment II (824.78 g/m2), treatment III (783.41 g/m2) and treatment I (230.14 g/m2). The difference between control and reclaimed ponds was highly significant at 1% level, but no significant differences among treatment II, III and IV were observed. Highly significant correlation at 1% was obtained between lablab production and various chemical parameters of soils and waters. High fish mortalities occurred in the control ponds due to poor conditions such as low pH coupled with abrupt change of the environment during heavy rains, but this was not observed in treatments II, III and IV. The fish survival and growth were significantly (1-5% level) can related to chemical parameters of the pond water during rearing period. The fish yield was highest in treatment II ) 408.3 kg/ha, closely followed by treatment IV (400.3 kg/ha) and treatment III (369.3 kg/ha). The control (Treatment I) had significantly lower yield (167.1 kg/ha) at 5 % level compared to treatments II, III, and IV, but no differences were obtained among treatments II, III and IV. If tilapia hat grew also included in the fish yield, treatment IV showed highest production. Highly significant correlation at 1% level was obtained between fish yield lablab production.